PENGARUH PENGGUNAAN LEMBAR KEGIATAN MAHASISWA (LKM) TERHADAP HASIL BELAJAR MATA KULIAH AKUNTANSI KEUANGAN MENENGAH I - Rochmawati, Rochmawati; Widayati, Irin; Kirwani, Kirwani (Jurnal Pendidikan Ilmu Sosial, 2018)
This study aims to determine the effect of learning outcomes on students who use Contextual Student Activities Sheet (CSAS/LKM) with students who do not use CSAS in intermediate financial accounting I lesson. During this time the teaching and learning process in the classroom using only literature books. The research method in this study was an experiment using a t test analysis tool. the value of t count is 127,098 supported by a significance of 0.001 â‰¤ 0.005 for students of class 2016 who are divided into experimental and control classes. The results of the study showed that there are effects of student learning outcomes using CSAS/LKM on student learning outcomes.